EFFECT OF STRATEGIC MINERAL MIXTURE ON THE PERFORMANCES OF SOW AND PIGLETS - SARMAH, B. K.; SAHARIA, J.; BORAH, S.; SARMA, B.C.; DEKA, I.; DUTTA, A.; GOSWAMI, J. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTAn experiment was carried out to see the effect of specific minerals on performancesof sow as well as piglets. A total of 10 pure bred Hampshire sows of first or secondfarrowing were randomly selected and placed under Experimental Group. Another 10 sows ofthe same breed and reproductive status served as Control. The animals were kept underintensive system in 30 sow unit, College of Veterinary Science, AAU, Guwahati. Animals wereoffered concentrate mixture two times a day – morning and evening. Sows underexperimental group were supplemented with strategic mineral mixture (AAUVETMIN) whileControl animals were supplemented commercial mineral mixture. The mean litter size atbirth in experimental and control group were 9.90 ± 0.67 and 8.90 ± 0.90 respectively. Meanlitter size at weaning was recorded, respectively as 8.70 ± 0.75 and 7.60 ± 0.54 inexperimental and control group. The mean litter weight and average individual body weight ofpiglets at birth and weaning in experimental group were 14.50 ± 1.01 & 85.62 ± 7.06 and1.48 ± 0.04 & 9.88 ± 0.12 kg while in control group respective values were 12.77 ± 1.14 &67.80 ± 5.92 and 1.46 ± 0.04 & 8.87 ± 0.41 kg. The ratio of male to female piglets at birthin experimental and control groups were 1 : 1.09 and 1 : 1.41. The corresponding values formale to female ratio at weaning were 1 : 1.18 and 1 : 1.24. The numbers of female pigletswere higher than male in both experimental and control groups. In experimental groupsurvivability rate from birth to weaning was recorded as 87.88% against 85.39% in controlgroup. The supplementation of strategic mineral mixture to the sows during pregnancy couldincrease the survivability rate by 2.49%.Key words: Mineral mixture, sow, litter size, litter weight, survival rate.